Catalytic Enantioselective Synthesis of Heterocyclic Vicinal Fluoroamines by Using Asymmetric Protonation: Method Development and Mechanistic Study. Issue 53 (18th August 2020) - Ashford, Matthew W.; Xu, Chao; Molloy, John J.; Carpenter‐Warren, Cameron; Slawin, Alexandra M. Z.; Leach, Andrew G.; Watson, Allan J. B.
Abstract: A catalytic enantioselective synthesis of heterocyclic vicinal fluoroamines is reported. A chiral Brønsted acid promotes aza‐Michael addition to fluoroalkenyl heterocycles to give a prochiral enamine intermediate that undergoes asymmetric protonation upon rearomatization. The reaction accommodates a range of azaheterocycles and nucleophiles, generating the C−F stereocentre in high enantioselectivity, and is also amenable to stereogenic C−CF3 bonds. Extensive DFT calculations provided evidence for stereocontrolled proton transfer from catalyst to substrate as the rate‐determining step, and showed the importance of steric interactions from the catalyst's alkyl groups in enforcing the high enantioselectivity. Crystal structure data show the dominance of noncovalent interactions in the core structure conformation, enabling modulation of the conformational landscape. Ramachandran‐type analysis of conformer distribution and Protein Data Bank mining indicated that benzylic fluorination by this approach has the potential to improve the potency of several marketed drugs. Abstract : Chiral Brønsted acid catalysis enables the synthesis of heterocyclic vicinal fluoroamines by asymmetric protonation. The reaction accommodates a range of azaheterocycles and nucleophiles, generating the C−F stereocentre in high enantioselectivity, and allows the formation of chiral C−CF3 bonds. DFT calculations provided insight into the reaction mechanism, and conformational control of the products is elucidated.